PERANCANGAN TAMPILAN APLIKASI UJIAN BERBASIS KOMPUTER UNTUK UJIAN HARIAN SEKOLAH MENENGAH ATAS - Nugrahaeni Puspita Dewi, Catur; Raafi'udin, Ridwan (Program Studi Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2018)
Information and communication technology develops and forces users to always improve the implementation of our technology. Almost in society both in the industry in business competition and education sector to improve educational services. Increasing number of students, it must be required to use technology in managing their daily educational activities. Today there are many high schools that implement computer based test, only limited for training and taking of national final exams. So, with a short time there are still many students who are not familiar with the form of computer based test. Although these schools already have computer laboratories. In this research, the tim will try to design a computer based test system for schools that already have computer laboratories to be able to produce a daily test model independently. This research will produce a model graphic user interface (GUI) that can support the daily exam process in school and is expected to help students to deal with other computer based test models. To produce a User Friendly display model, many survey of students and teachers was conducted on the form of the test display with various features, such as photos, clocks, countdown timers, formulas, and standard values or constants.